1986
DOI: 10.1111/j.1476-5381.1986.tb09476.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of BRL 34915 and verapamil on electrical and mechanical activity in rat portal vein

Abstract: 1 The effects of the novel anti-hypertensive agent BRL 34915, (±) 6-cyano-3,4-dihydro-2,2-dimethyl-trans-4-(2-oxo-1-pyrrolidyl)-2H-benzo [b]pyran-3-ol, have been compared with those of verapamil on rat isolated portal vein. 2 BRL 34915 produced a concentration-dependent reduction in mechanical responses to noradrenaline but had relatively little inhibitory effect on K+-induced contractions. Verapamil reduced the magnitude of both noradrenaline and K+-induced mechanical responses. 3 BRL 34915 delayed the appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
247
0
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(277 citation statements)
references
References 9 publications
29
247
0
1
Order By: Relevance
“…In these experiments 86Rb was used as a K+ marker and the technique of Hamilton et al (1986) was broadly followed. Myometrial strips were removed from 4 day-22 pregnant rats on each of 2 days and assigned to the following experimental groups: day I -PSS, PSS + BRL 34915 vehicle, BRL 34915 (10 gM); day 2 -PSS, BRL 34915 (I JLM), BRL 34915 (IOtM), oxytocin (0.2 or 20 nM).…”
Section: Rb Effluxmentioning
confidence: 99%
See 2 more Smart Citations
“…In these experiments 86Rb was used as a K+ marker and the technique of Hamilton et al (1986) was broadly followed. Myometrial strips were removed from 4 day-22 pregnant rats on each of 2 days and assigned to the following experimental groups: day I -PSS, PSS + BRL 34915 vehicle, BRL 34915 (10 gM); day 2 -PSS, BRL 34915 (I JLM), BRL 34915 (IOtM), oxytocin (0.2 or 20 nM).…”
Section: Rb Effluxmentioning
confidence: 99%
“…It has been suggested that these inhibitory effects are achieved by the opening of K+-channels so that the membrane potential of smooth muscle cells is held at or close to the potassium equilibrium potential (EK) (Allen et al, 1986;Hamilton et al, 1986;Weir & Weston, 1986a,b). Support for this idea comes from 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efflux of operated Ca2+ channels (VOC). Thus cromakalim K+ ions from the vascular smooth muscle cell hyperinhibits contractions induced by KCl, although high polarises the membrane towards the K+ equilibrium concentrations (>60mM) of KCl, produce contracpotential (Hamilton et al, 1986; tions which are resistant to cromakalim Clapham & Wilson, 1987 Cromakalim also inhibits contractions induced by receptor agonists such as noradrenaline, histamine, 5-hydroxytryptamine (5-HT) and angiotensin II (Clapham & Wilson, 1987;Cain & Nicholson, 1988;Cook et al, 1988;Wilson, 1988), even though contractions to these agents are less dependent on depolarisation than the equivalent contractions to KCI (Mulvany et al, 1982;Bolton et al, 1984;Haeusler, 1985;Neild & Kotecha, 1987). Unlike contractions to KCl, contractions to all concentrations of the receptor agonists are inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the ability of cromakalim to open smooth muscle cell membrane K+ channels underlies its relaxant effect not only in rabbit, rat and guinea-pig isolated blood vessels (Coldwell & Howlett, 1986;Hamilton et al, 1986;Quast, 1987), but also in rat isolated uterus (Hollingsworth et al, 1987), guineapig trachealis (Allen et al, 1986) and guinea-pig and pig urinary bladder (Foster & Brading, 1987).…”
Section: Introductionmentioning
confidence: 99%